Pengaruh Pengalaman, Kepuasan dan Niat Word Of Mouth Terhadap Loyalitas Pelanggan di Bank Digital - Dessy Setyaningrum; Gilang Pratama Hafidz (MES Bogor, 2026)
Customer satisfaction in digital banking plays an important role in ensuring the sustainability of banking services. Satisfied customers tend to continue using the service and recommend it to others, which can expand the customer base. This study aims to analyze the relationship between customer experience, customer satisfaction, and word of mouth intention in influencing customer loyalty. This study uses a quantitative approach with a purposive sampling method, involving 240 digital bank customer respondents in JABODETABEK. Data collection was carried out through questionnaires, and data analysis used the Structural Equation Modeling (SEM) method. The results of the study indicate that customer experience, customer satisfaction and word of mouth intention have a positive and significant influence on customer loyalty. However, this study has limitations, such as only focusing on the customer perspective without considering external factors such as government regulations and technological developments that can affect customer loyalty. Therefore, further research is recommended to use a longitudinal method to analyze changes in customer behavior over time and consider external variables that can moderate the relationship between experience, satisfaction, and intention to share recommendations with customer loyalty.